PENGARUH LKS ICT MENGINTEGRASIKAN MSTBK PADA MATERI GERAK, GRAVITASI, DAN ENERGI TERHADAP KOMPETENSI FISIKA SISWA KELAS XI DI SMAN 1 PADANG - Yudya Azzahri; Akmam Akmam; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2015)
Integrated students competence is important in 2013 curriculum. In fact, integration of students competence does not conducted yet. One of the effort that can be done to solve the problem was to apply students worksheet by integrating the various of material in Physics learning. This students worksheet was predicted effective to increase Physics competence of students. The purpose of this research was to know the effect of using students worksheet by integrating Mathematics, Science, Technology, Disaster, and Character value (MSTDC) at topics of motion, gravitation, and energy based on Information and Communication Technology (ICT) toward Physics competence of students at eleventh class of MIA SMAN 1 Padang. The design of Quasi experiment research was randomized control group only design. Population of  research was students at eleventh class of MIA SMAN 1 Padang that listed in 2014/2015 learned years. Sample was gotten with purpossive sampling technique. Data of research includes knowledge, attitude, and skill domain. This data were analyzed by applying compare mean test. Based on the result of data analysis can be stated two of research results. First, the competence of students used ICT students worksheet by integrating MSTDC had mean value at knowledge, attitude, and skill domain respectly 91.38; 89.45;91.67. Second, the use of ICT students worksheet by integrating MSTDC at topics of, gravitation, and energy give significant effect toward Physics competence of students at eleventh class of MIA SMAN 1 Padang  on the real  level  of  0,05.